2022
DOI: 10.1158/1541-7786.mcr-21-0477
|View full text |Cite
|
Sign up to set email alerts
|

VPRBP Functions Downstream of the Androgen Receptor and OGT to Restrict p53 Activation in Prostate Cancer

Abstract: Androgen receptor (AR) is a major driver of prostate cancer (PCa) initiation and progression. O-GlcNAc transferase (OGT), the enzyme that catalyses the covalent addition of UDP-N-acetylglucosamine (UDP-GlcNAc) to serine and threonine residues of proteins, is often highly expressed in PCa with its expression correlated with high Gleason score. In this study we have identified an AR and OGT co-regulated factor, Vpr (HIV-1) binding protein (VPRBP) also known as DDB1 and CUL4 Associated Factor 1 (DCAF1). We show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…2A–D ), and Rheb primarily expressed in the cytoplasm (Supplementary Fig. S2E ), which was consistent with observations of previous studies [ 21 , 22 , 38 ]. Co-localization analysis revealed that DCAF1 and Rheb co-localized in the cytoplasm (Fig.…”
Section: Resultssupporting
confidence: 92%
“…2A–D ), and Rheb primarily expressed in the cytoplasm (Supplementary Fig. S2E ), which was consistent with observations of previous studies [ 21 , 22 , 38 ]. Co-localization analysis revealed that DCAF1 and Rheb co-localized in the cytoplasm (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Zhang et al also identified ADH5 as a prognosis-related gene by bioinformatics analysis [ 20 ]. Studies by Ninu Poulose et al have shown that VPRBP/DCAF1 promotes prostate cancer cell proliferation by inhibiting p53 activation under the influence of AR and OGT [ 21 ]. Furthermore, MYO6 is strongly associated with Gleason score in prostate cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…DCAF1 and CRL4-DDB1-Rbx1 jointly form E3 ubiquitin ligase 17 , which is involved in the regulation of life activities such as cell growth, development, differentiation and apoptosis 16,18,19 . Previous studies have found that DCAF1 is closely related to the occurrence and development of glial cancers, colon cancer and prostatic cancer [20][21][22] . However, the role and prognosis of DCAF1 in GC are still lacking.…”
Section: Introductionmentioning
confidence: 94%